Cryptographic hash function: A high level view - Alkandari, Abdulaziz Ali; Alshaikhli, Imad Fakhri Taha; Alahmad, Mohammad A. (2013)
Cryptographic hash function verifies data integrity and sender identity or source of information. The task is accomplished by taking a variable bit patterns as an input then produces a fixed bit patterns of output. This paper provides a detailed overview to include classification, properties, constructions, attacks, applications and an overview of a selected dedicated cryptographic hash function.